TANATOLOGICAL MOTIVES IN “TALES OF THE PECULIAR” BY R. RIGGS - Алексенко, Виталия (SWorldJournal, 2021)
The aim of the article is to consider the motive of death in “Tales of the Peculiar” by Ransom Riggs and its role in the plot-image system. The researcher focuses on two stories - "The fork-tongued princess" and "The woman who befriended ghosts." R. Riggs